Land Acquisition Of Former Building Use Rights (HGB) For The Construction Of Permanent Housing After The Earthquake In Tondo-2 Area, Hammer - Puguh Aji Hari Setiawan; Bernadete Nurmawati; KMS Herman; Nomensen Sinamo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
About 50,000 people were displaced by a 7.4 magnitude earthquake, tsunami, and liquefaction 10 km north of Palu City, Central Sulawesi Province, on September 28, 2018. The tragedy damaged many civic, social, and critical infrastructure in Palu City and nearby regions. The national government, Sulawesi provincial administration, and Palu city government are developing a relocation plan for earthquake, tsunami, and liquefaction-affected residents. This strategy will restore and rehabilitate sites like Palu City's Tondo-2 Area. To move affected residents to a safe area quickly after a disaster, land acquisition must be accelerated. This research aims to determine how the earthquake influenced the acquisition of ex-HGB land for Huntap's development in the Tondo-2 Area, Palu, and how such land acquisition was affected by the earthquake. Normative legal research is used. This study used a wide range of relevant books and scholarly papers. The Governor's development block authorized Huntap's construction in Tondo-2, as stated in Governor Decree No. 369/516/DIS-BMPR G.ST/2018, which determines the location (penlok) of land for permanent residential sites for disaster-affected communities in Central Sulawesi Province. The release or transfer of HGB from PT Sinar Putra Murni and PT Sinar Waluyo gave this 65.3-hectare state land its status. The community claims to own the land, and PT Sinar Putra Murni and PT Sinar Waluyo want compensation, which could lead to a lawsuit. Since the two firms no longer own the land, their legal chances are slim. If the firm continues to sue over land acquisition, Huntap can still be built under Law Number 2 of 2012 on Land Acquisition for Development for the Public Interest